2013
DOI: 10.4317/medoral.18298
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis, jawbones and periodontal disease

Abstract: The association between osteoporosis and jawbones remains an argument of debate. Both osteoporosis and periodontal diseases are bone resorptive diseases; it has been hypothesized that osteoporosis could be a risk factor for the progression of periodontal disease and vice versa. Hypothetical models linking the two conditions exist: in particular, it is supposed that the osteoporosis-related bone mass density reduction may accelerate alveolar bone resorption caused by periodontitis, resulting in a facilitated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 47 publications
2
87
0
1
Order By: Relevance
“…20,21 However, some animal studies have reported positive correlation of osteoporosis and alveolar bone changes, and periodontal bone loss. 7,9,10,14 Therefore, there is a clear need to clarify the effect of estrogen deficiency on maxillary and mandibular alveolar bones. Given trabecular bone is believed to be more susceptible to be affected by estrogen deficiency than cortical bone, 22 maxillary bone, especially the porous, posterior maxillary region may be regarded as a more sensitive location for estrogen deficiency, compared with mandibular bone.…”
mentioning
confidence: 99%
“…20,21 However, some animal studies have reported positive correlation of osteoporosis and alveolar bone changes, and periodontal bone loss. 7,9,10,14 Therefore, there is a clear need to clarify the effect of estrogen deficiency on maxillary and mandibular alveolar bones. Given trabecular bone is believed to be more susceptible to be affected by estrogen deficiency than cortical bone, 22 maxillary bone, especially the porous, posterior maxillary region may be regarded as a more sensitive location for estrogen deficiency, compared with mandibular bone.…”
mentioning
confidence: 99%
“…Osteoporosis may affect the jawbones 16 . In addition, these modifications might potentially speed up the periodontal tissues breakdown caused by periodontitis 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in bone mineral density in osteoporosis alters the trabecular pattern and may lead to a more rapid jawbone resorption caused by periodontal disease, due to the invasion of periodontal pathogenic bacteria. Conversely, the invasion of periodontal pathogenic bacteria may alter the normal homeostasis of the alveolar bone, increasing the osteoclastic activity and reducing the local and systemic bone density [6]. Pepelasi et al [7] suggested that postmenopausal women with osteoporosis had greater gingival inflammation, periodontal attachment loss, and gingival recession than postmenopausal women with a normal bone mineral density (BMD).…”
Section: Introductionmentioning
confidence: 99%